TRAINING ON WRITING SCIENTIFIC JOURNAL ARTICLES FOR TEACHERS OF SMA NEGERI 5 PALANGKA RAYA - Karelius; Revianti Coendraad (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
The current teacher if you want promotion should attach his scientific work to Group IV a to IV b but in Ministerial Decree N0.16 of 2009 scientific papers have become the requirement of the increase of Group III b to III c, then the teacher must have the ability to make the work scientific writing. Community service is aimed to provide knowledge and skills for high school teachers NEGERI 5 Palangka especially those who follow the training of writing scientific papers, where later scientific papers produced in the form of articles are expected to be published in local journals with ISSN. Participants of the event generally consist of junior teachers who are adjusted to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform. 16 Year 2009 About the Functional Position of Teachers and Agencies Credit which, among others, change the promotion and class of teachers to rise the class of IV a must make scientific papers now must be from class III B to III C. Training methods using lectures and frequently asked questions, demonstrations and practice.